1804 Which Musical Tune Improves Synchronization of Respiratory Support During Simulated Cardio-Pulmonary Resuscitation of Neonates?. (October 2012) - Schmölzer, G; Roehr, CC; Wong, C; Dawson, J; Davis, P
Abstract : Introduction: The need to provide chest compressions and assisted inflations occurs infrequently during neonatal resuscitation. A mannequin study of cardiopulmonary resuscitation (CPR) in adults showed that listening to music improved the coordination of inflations and chest compressions. Aim: To compare several musical tunes during simulated CPR and the effect on coordinating inflations and chest compression during two helper CPR. Methods: Five different tunes ("I will survive" (120 bpm), "Radetzkimarsch" (105 bpm), "Jingle Bells" (120 bpm), "Stayin' alive" (105 bpm), and "S.O.S." (120 bpm)) were played during simulated neonatal CPR. The order in which the tunes were played was randomized. Mask leak and tidal volume was measured using a respiratory function monitor and used to investigate the degree of synchronization of two-helper CPR. Measurements were recorded at baseline (no music) and with individual tunes, each played for one minute during which CPR was provided by neonatal staff. Results: During baseline median (SD) chest compressions and inflations were 80 (6) and 28 (2) per minute, respectively. 43% of chest compressions occurred during expiration, 16% during inspiration and 41% between expiration and inspiration. Only listening to "S.O.S." improved the number of delivered chest compressions and inflations significantly compared to baseline. Mask leak and tidal volume delivery was similar while listening to any of the five musical tunes. Conclusion: ABBA's S.O.S significantly improved the number of chest compressions and inflations. Musical mnemonics apparently have the potential to improve mask ventilation when cardiac compressions are required. Their use should be further investigated.